Different cutoffs of the reflux finding score for diagnosing laryngopharyngeal reflux disease should be used for different genders. (2nd September 2018) - Gao, Cheng-Kai; Li, Yan-Fei; Wang, Lu; Han, Xiao-Yan; Wu, Ting; Zeng, Fang-Fang; Li, Xiang-Ping
Abstract: Objectives: To assess the differences in Reflux Finding Score (RFS) between the genders and determine the suitable RFS threshold for diagnosing laryngopharyngeal reflux disease (LPRD) in each gender. Methods: Asymptomatic volunteers and patients with LPRD, confirmed with an oropharyngeal Dx-pH monitoring system, were included. All study subjects underwent transnasal flexible fiber-optic video laryngoscopy. Reliability was assessed with intra-class correlation coefficients (ICCs) and Bland-Altman plots. The RFS cutoffs for determining the presence and absence of LPRD between the two genders were examined by receiver operating characteristic (ROC) analysis. Results: One hundred seven asymptomatic volunteers and fifty-five LPRD patients were recruited. The mean RFS for LPRD subjects (9.4 ± 3.2) was significantly higher than that for control subjects (7.1 ± 2.6; p  < 0.001). The mean RFS for asymptomatic females (6.1 ± 2.7) was significantly lower than that for males (7.7 ± 2.5; p  < 0.001). The mean RFS for female subjects with LPRD (7.8 ± 2.6) was lower than that for males (11.0 ± 2.8; p  < 0.001). According to ROC analysis, the best cutoffs were 9.0 for males and 6.0 for females. Conclusions: There was a significant difference in the RFS cutoff between the genders. For male subjects, we recommend a cutoff of 9.0 for diagnosing LPRD, and for female subjects, we recommend a cutoff of 6.0.